The Charter Granted by Their Majesties King William and Queen Mary to the Inhabitants of the Providence of the Massachussets Bay in New England 271-72 (1726) - (:unkn) unknown (My University, 1719)
An Act For the Punishing and Preventing of Duelling: That whoever ... fight a duel, combat, or engage in a rencounter with rapier, or small-sword, back-sword, pistol, or any other dangerous weapon, to the danger of life, mayhem, or wounding of the parties, or the affray of his Majesty's good subjects, (although death doth not thereby ensue) and be thereof convicted, by due course of law, before the Court of Assize, or Court of General Sessions of the Peace, in the respective Counties of this Province, shall be punished by fine, not exceeding a hundred pounds, imprisonment, not exceeding six months, or corporally punished...
Keywords: DUELING